A meta-analysis of the international gender wage gap - Doris Weichselbaumer; Rudolf Winter-Ebmer (Institute for Advanced Studies (IHS), 2003)
Since the early seventies, hundreds of authors have calculated gender wage differentials between women and men of equal productivity. This meta-study provides a quantitative review of this vast amount of empirical literature on gender wage discrimination as it concerns differences in methodology, data, countries and time periods. We place particular emphasis on a proper consideration of the quality of the underlying study which is done by a weighting with quality indicators. The results show that data restrictions have the biggest impact on the resulting gender wage gap. Moreover, we are able to show what effect a misspecification of the underlying wage equation - like the frequent use of potential experience - has on the calculated gender wage gap. Over time, raw wage differentials world-wide have fallen substantially; however, most of this decrease is due to an increased labor market productivity of females.
Keywords: J16; J31; J71; 330; gender wage differential; meta-analysis; Lohndifferenzierung; Geschlecht; Fraueneinkommen; Empirische Methode; Modellierung; Welt